Isolation of alginate-assimilating marine bacterium and the extraction, semi-purification and partial characterization of its alginate lyase - Narciso, Joemark T. (Marine Science Institute, College of Science, University of the Philippines Diliman, 2016)
Brown seaweeds possess phytochemicals and complex polysacchrides that have potential applications for food, beverage and pharmaceutical industries. Alginate is one of these complex polysaccharides found in the cell walls of brown macroalgae. They are promising macromolecules because they are produced abundanty by brown seaweeds. Oligo-alginates produced by algnate lyases are value added products that are novel sources of functional oligosaccharides. Alginate lyases are mainly purified from marine mollusks, marine algae, and other members of the phylum Bacteroidetes. Additional purification and characterization is needed to confirm the molecular weight of the alginate lyase. Additional assays should be done to further reveal its enzymatic properties. Analyses of substrate specifcities and its reaction byproducts are also needed to determine whether the enzyme is endolytic or exolytic. The structure-function relationship of the substrate, enzyme and hydrolysate should be further investigated. To increase the production of the alginate lyase, the entire coding region of the enzyme should be expressed in recombinant systems such as the E. coli.